Tactics of Surgical Treatment of Patients with Consequences of Cranial Value Burns - Madazimov Komiljon Muminovich (Academia One, 2023)
The authors presented the first clinical experience of using a new method of plastic surgery to eliminate the consequences of burns in the cranial vault area. 32 patients were operated on using the new method. The proposed method of plastic surgery of the cranial vault with stretched tissues in 28 (87.5%) patients out of 32 allowed to achieve good functional and aesthetic results.
Keywords: cranial vault; consequences of burns; alopecia